Study the following functions
5) f(x) = I2x - 3Ie-1/x
"\\lim_{x\\to +0} f(x) =|2\\cdot 0-3|\\cdot e^{\\frac{-1}{+0}}=3\\cdot e^{-\\infty}=3\\cdot 0=0"
"\\lim_{x\\to -0} f(x) =|2\\cdot 0-3|\\cdot e^{\\frac{-1}{-0}}=3\\cdot e^{\\infty}=3\\cdot \\infty=\\infty"
4 Oblique asymptote
"f(x)=\\begin{cases}\n (2x-3)\\cdot e^{-\\frac{1}{x}},\\space x\\ge1.5\\\\(3-2x)\\cdot e^{-\\frac{1}{x}},\\space x<1.5\\ \\end{cases}"
"\\lim_{|x|\\to \\pm \\infty} e^{\\frac{-1}{x}}=e^{-\\frac{1}{\\pm \\infty }}=e^0=1"
so
y=2x-3 - right oblique asymptote
y=3-2x -left oblique asymptote
5 Zeros
f(x)=|2x-3|"\\cdot e^{-\\frac{1}{x}}=0 \\iff x=1.5"
{1.5} - set of zeros of the function;
6 Sign
|2x-3| "\\ge 0,\\space e^{-\\frac{1}{x}}\\ge 0\\implies f(x) \\ge 0" everywhere
5 Derivative
1) x>1.5 f'(x)="\\left( (2x-3)\\cdot e^{\\frac{-1}{x}} \\right)'=2\\cdot e^{-\\frac{1}{x}}+(2x-3)\\cdot e^{-\\frac{1}{x}}\\cdot \\left( \\frac{-1}{x} \\right)'=\\frac{2x^2+2x-3}{x^2}\\cdot e^\\frac{-1}{-x}"
2.x<1.5 f'(x)="\\left( (3-2x)\\cdot e^{\\frac{-1}{x}} \\right)'=2\\cdot e^{-\\frac{1}{x}}+(2x-3)\\cdot e^{-\\frac{1}{x}}\\cdot \\left( \\frac{-1}{x} \\right)'=-\\frac{2x^2+2x-3}{x^2}\\cdot e^\\frac{-1}{-x}"
5.1 Zeros of derivative
2x2+2x-3=0;
"x_{1,2}=\\frac{-2 \\pm\\sqrt{4+24}}{4}=\\frac{-1\\pm \\sqrt 7}{2}"
both values are less than 1.5
5.2 Sign of derivative and monotony, extremes
"x \\in \\left ( -\\infty , \\frac{-1-\\sqrt 7}{2} \\right)" f'(x)<0 f(x) decreasing
"x \\in \\left ( \\frac{-1-\\sqrt 7}{2} , 0 \\right ) \\cup \\left(0,\\frac{-1+\\sqrt 7}{2} \\right)" f'(x)>0 f(x) increaing
"x \\in \\left(\\frac{-1+\\sqrt 7}{2},\\space 1.5 \\right)" f'(x)<0 f(x) decreasing
"x\\in (1.5, \\infty)" f'(x)>0 f(x) increasing
"x_{1}= \\frac{-1-\\sqrt 7}{2}" - point of minimum
"x_{1}= \\frac{-1+\\sqrt 7}{2}" - point of local maximum
6 Second derivative
1) x>1.5
f''(x)="\\left((2+\\frac{2}{x}-\\frac{3}{x^2})\\cdot e^{-\\frac{1}{x}}\\right)'=\\left( -\\frac{2}{x^2} +\\frac{6}{x^3}\\right)\n\\cdot e^{-\\frac{1}{x}}+(2+\\frac{2}{x}-\\frac{3}{x^2})\\cdot\\left( e^{-\\frac{1}{x}} \\right)'="
"\\left((2+\\frac{2}{x}-\\frac{3}{x^2})\\cdot e^{-\\frac{1}{x}}\\right)'=\\left( -\\frac{2}{x^2} +\\frac{6}{x^3}\\right)\n\\cdot e^{-\\frac{1}{x}}+(2+\\frac{2}{x}-\\frac{3}{x^2})\\cdot e^{-\\frac{1}{x}}\\cdot \\frac {1}{x^2}=\\\\\n=\\frac{-2x^2+6x+2x^2+2x-3}{x^4}\\cdot e^{-\\frac{1}{x}}=\\frac{8x-3}{x^4}\\cdot e^{-\\frac{1}{x}}"
2) x<1.5
f''(x)="-\\frac{8x-3}{x^4}\\cdot e^{-\\frac{1}{x}}"
6.1 Zeros of second derivative
f''(x)=0 "\\iff x=\\frac{3}{8}<1.5"
Sign of f''(x)
"x \\in (-\\infty, 0)" f''(x)>0, f(x) is convex
"x\\in(0,\\frac{3}{8})" f"(x)>0 f(x) is convex
"x\\in(\\frac{3}{8},1.5)" f''(x)<0 f(x) is concave
"x\\in (1.5,\\infty)" f''(x)<0 f(x) ic convex
x3,4=3/8,1.5 - points d'inflexion
Scetch of graph
Comments
Leave a comment